BODY MASS INDEX (BMI) OF CHILDREN WITH TETRALOGY OF FALLOT (TOF) - Ovin Nada Saputri; Viskasari P. Kalanjati; Mahrus A. Rahman (Majalah Biomorfologi, 2020)
Background: Malnutrition is a common cause of morbidity and mortality amongst children with TOF. Objective: To analyze the BMI profile of children with TOF aged 0 – 18 years at Pediatric Department, Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. Materials and Methods: A cross-sectional study of the BMI from the medical record of TOF patients aged 0 – 18 years at the Pediatric Department, Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, since January 2016 to December 2017 was conducted. The data included gender, age group, demographic distribution, weight, and height. BMI was calculated by WHO formula reference; body weight (kg) divided by body height squared (m2), which was converted into z-score histogram. BMI classification was guided by the Government’s Anthropometry Standards for Nutritional Status Assessment. Result: From 84 TOF patients, there were 43 males (51%) and 41 females (49%). The most dominant age group was 0 – 4 years old (n=47;56%). The majority of patients were from outside of Surabaya (n=64;76.2%). Based on their BMI, 36 patients (42.9%) had severe underweight, 10 patients (11.9%) were underweight, and 35 patients (41.7%) were normal, whilst the rests (3.6%) were overweight. Conclusion: The number of male patients was slightly higher than female patients. The majority of TOF patients were 0 – 4 years old and resided out town of Surabaya. The predominant BMI found was the underweight and severe underweight below normal BMI.